I was just in Shock: Identity Work by European Skilled Migrants Following the Brexit Referendum - Miedtank, Tina; Jonczyk Sédès, Claudia; Oliver, David (My University, 2020)
This study examines how skilled EU migrants living in the UK respond to and cope with the result of the Brexit referendum in terms of their identities. Our study identifies four distinctive reaction patterns among EU migrants depending on the degree to which they interpreted the Brexit vote as a threat to their identity, and the number of national affiliations they held. We refer to these as EU Patriots, Local Cosmopolitans, Home Country Patriots, and Global Citizens. Each of these distinctive reaction patterns involves different forms of identity work and agency in skilled migrant's professional and personal spheres. Our study provides insights into the way in which identity impacts migrants and expatriates, as well as to the interplay between contextual constraints and agency in the face of identity threats.
, 2020
Keywords: Identity work. EU skilled migrants; Brexit; qualitative